Comparative Analysis Impulse Purchases of Millennials and Generation Z on the Live Shopping Platform Tiktok - Febriansyah, Farah Azzahra; Chalid, Chalid; Hilmansyach, Muhammad Alvin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research was conducted to ascertain the impact of Live shopping on the Tiktok platform and to determine the behavioral comparison between Millennials and Generation Z, with Tiktok Live Shopping as an independent variable. This study collects data online using quantitative methods surveys of customers who have shopped on the TikTok platform as objects. The data analysis used is a statistical test to determine the validity and reliability of and regression test to see the relationship between variables and an independent sample t-test to see the difference between Millennials and Gen Z. The outcomes demonstrated a strong and favorable influence between Tiktok Live shopping but there was no difference in influence between millennials and Gen Z.